On the Oxidation of Different Iminic Bonds by Excess of 3-Chloroperbenzoic Acid - Troisi, Luigino; Carrozzo, Marina M.; Citti, Cinzia; Falcicchio, Aurelia; Mansueto, Rosmara; Rosato, Francesca; Cannazza, Giuseppe (Synlett, 2013)
In the present work the behavior of different substituted iminic bonds toward the oxidative action of 3-chloroperbenzoic acid is reported. The C=N bond was or was not oxidized to oxaziridines, amides, oximes, nitroso-, nitro-, and azodioxy compounds depending on the substituents at the iminic group and on the imine/MCPBA stoichiometric ratio.
Keywords: imines; oxidation; oxaziridines; C-nitroso compound; oximes